Comprehensive analysis of key genes, microRNAs and long non‐coding RNAs in hepatocellular carcinoma. Issue 9 (31st July 2018) - Shi, Baoqi; Zhang, Xuejun; Chao, Lumeng; Zheng, Yu; Tan, Yongsheng; Wang, Liang; Zhang, Wei
Abstract : Human hepatocellular carcinoma (HCC) is a common aggressive cancer whose molecular mechanism remains elusive. We aimed to identify the key genes, microRNAs (miRNAs) and long non‐coding RNAs (lncRNAs) involved with HCC. We obtained mRNA, miRNA and lncRNA profiles for HCC from The Cancer Genome Atlas and then identified differentially expressed mRNAs (DEmRNAs), miRNAs (DEmiRNAs) and lncRNAs (DElncRNAs). We performed functional annotation of DEmRNAs and then constructed HCC‐specific DEmiRNA–DEmRNA, DEmiRNA–DElncRNA and DElncRNA–DEmiRNA–DEmRNA interaction networks. We searched for nearby target cis ‐DEmRNAs of DElncRNAs and performed receiver operating characteristic and survival analyses. A total of 1239 DEmRNAs, 33 DEmiRNAs and 167 DElncRNAs in HCC were obtained. Retinol metabolism [false discovery rate (FDR) = 7.02 × 10 −14 ] and metabolism of xenobiotics by cytochrome P450 (FDR = 7.30 × 10 −11 ) were two significantly enriched pathways in HCC. We obtained 545 DEmiRNA–DEmRNA pairs that consisted of 258 DEmRNAs and 28 DEmiRNAs in HCC. mir‐424, miR‐93 and miR‐3607 are three hub DEmiRNAs of the HCC‐specific DEmiRNA–DEmRNA interaction network. HAND2‐AS1/ENSG00000232855–miR‐93– LRAT/RND3, ENSG00000232855–miR‐877– RCAN1 and ENSG00000232855–miR‐224– RND3 interactions were found in the HCC‐specific DElncRNA–DEmiRNA–DEmRNA interaction network. A total of three DElncRNA–nearby target DEmRNA pairs (HCG25– KIFC1, LOC105378687– CDC20 and LOC101927043– EPCAM ) in HCC were obtained. Diagnostic and prognostic values of several selected DElncRNAs, DEmRNAs and DEmiRNAs for HCC were assessed. Our study identified several DEmRNAs, DEmiRNAs and DElncRNAs with great diagnostic or prognostic value for HCC, which may facilitate studies into the molecular mechanisms, and development of potential biomarkers and therapeutic target sites for HCC. Abstract : Human hepatocellular carcinoma (HCC) is a common aggressive cancer whose molecular mechanism remains elusive. Our study identified several mRNAs, miRNAs and lncRNAs with great diagnostic or prognostic value for HCC, which may facilitate studies into the molecular mechanism, and development of potential biomarkers and therapeutic target sites for HCC.